The War Has Brought Peace to Mexico : World War II and the Consolidation of the Post-Revolutionary State - Jones, Halbert, 1977- (Book collections on Project MUSE., 2014)
Though the war years in Mexico have attracted less attention than other periods, this book shows how the crisis atmosphere of the early 1940s played an important part in the consolidation of the post-revolutionary regime.